2008
DOI: 10.1016/j.immuni.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Costimulatory Ligand CD70 on Steady-State Dendritic Cells Breaks CD8+ T Cell Tolerance and Permits Effective Immunity

Abstract: Steady-state dendritic cells (DCs) maintain peripheral T cell tolerance, whereas mature DCs generate immunity. CD70 is a costimulatory ligand acquired upon DC maturation. To determine its impact on T cell fate, we have generated mice that constitutively express CD70 in conventional DCs (cDCs). In these mice, naive CD4+ and CD8+ T cells spontaneously convert into effector cells. Administration of peptide without adjuvant, which is ordinarily tolerogenic, elicited tumor-eradicating CD8+ T cell responses and robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
149
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 50 publications
12
149
0
Order By: Relevance
“…5B). Blocking of CD70 caused a 6-to 7-fold reduction of tetramer + cells, which is in agreement with studies showing that CD27 provides crucial costimulation for CD8 + T cell differentiation and memory formation (7,34,35). Remarkably, CD8 T cell priming was abolished by blockade of CCL3 or its receptor CCR5, whereas neutralization of CCL4 inhibited priming by only ∼40%.…”
Section: Efficient In Vitro Priming Of Naive Cd8 T Cells Requires Il-supporting
confidence: 90%
“…5B). Blocking of CD70 caused a 6-to 7-fold reduction of tetramer + cells, which is in agreement with studies showing that CD27 provides crucial costimulation for CD8 + T cell differentiation and memory formation (7,34,35). Remarkably, CD8 T cell priming was abolished by blockade of CCL3 or its receptor CCR5, whereas neutralization of CCL4 inhibited priming by only ∼40%.…”
Section: Efficient In Vitro Priming Of Naive Cd8 T Cells Requires Il-supporting
confidence: 90%
“…Interestingly, the requirement for 4-1BB costimulation during the primary response to influenza virus is greater during infection with a more virulent strain of virus, consistent with the higher expression of 4-1BB on activated T cells from mice bearing a higher viral load (13). Although the lack of CD27 signaling results in suboptimal CD8 T cell responses (12,(14)(15)(16)(17), deliberate triggering of CD27 by administration of soluble rCD70 (18) or through transgenic expression of CD70 on DCs (19) prevents tolerance induced by injection of a peptide Ag and allows the generation of a population of effector and memory CD8 T cells. Similarly, 4-1BB triggering was shown to prevent peptide-induced CD8 T cell tolerance (20) and augment effector and memory responses following peptide or DC immunization (21)(22)(23).…”
mentioning
confidence: 76%
“…Many studies have demonstrated that anti-tumor immunity and the ability to break tolerance could be enhanced by co-delivering additional immunomodulator genes, such as interleukin-2, interleukin-12, interleukin-15, CD70 and other activators, to DCs. 5,[57][58][59][60] We are currently conducting experiments to evaluate the anti-tumor immunity generated by the co-delivery of a tumor antigen and an immuomodulator using this DC-directed lentivector system.…”
Section: Discussionmentioning
confidence: 99%